STRATEGI KERJA PRAKTEK DENGAN TEKNIK UMPAN BALIK DAPAT MENINGKATKAN GURU GURU SD NEGERI 163083 TEBING TINGGI DALAM MENYUSUN RPP INOVATIF TAHUN 2018 - Setyo Sutarno (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2018)
ABSTRACTSchools as an educational institution or institution should ideally be able to carry out the process of education, socialization and transformation. The framework of thinking mentioned above directs the writer to formulate the hypothesis of action in this study, namely: Strategic Work Practice with the Feedback technique can increase teacher teachers in SD Negeri 163083 Tebing Tinggi in preparing an Innovative RPP. The researcher / supervisor collects each lesson plan that the teacher has made. From the results presented, conclusions can be drawn that the hypothesis of action has been proven, Performance indicators At least 85% of teachers show good commitment in preparing Innovative RPPs (average value 4.00-5.00) on a scale of 1-5 , reached at the end of the third cycle with an achievement of 94%.Keywords: Strategy, Innovative, Engineering ABSTRAKSekolah sebagai suatu institusi atau lembaga pendidikan idealnya harus mampu melakukan proses edukasi, sosialisasi, dan transformasi. Kerangka berpikir tersebut di atas mengarahkan penulis untuk merumuskan hipotesis tindakan dalam penelitian ini yaitu : Strategi Kerja Praktek dengan teknik Umpan Balik dapat meningkatkan guru guru SD Negeri 163083 Tebing Tinggi dalam menyusun RPP Inovatif. Peneliti/supervisor mengumpulkan masing-masing sebuah RPP yang telah dibuat guru. Dari hasil-hasil yang dipaparkan, dapat dibuat simpulan bahwa hipotesis tindakan telah terbukti, Indikator kinerja Sekurang-kurangnya 85% guru menunjukkan komitmen yang baik dalam menyusun RPP Inovatif (nilai rata-rata 4,00-5,00) dalam skala 1-5, tercapai pada akhir siklus III dengan pencapaian 94%Kata Kunci: Strategi, Inovatif, Teknik